Creating solvation environments in heterogeneous catalysts for efficient biomass conversion - Sun, Qi (Nat Commun, 2018)
Chemical transformations are highly sensitive toward changes in the solvation environment and solvents have long been used to control their outcome. Reactions display unique performance in solvents like ionic liquids or DMSO, however, isolating products from them is cumbersome and energy-consuming. Here, we develop promising alternatives by constructing solvent moieties into porous materials, which in turn serve as platforms for introducing catalytic species. Due to the high density of the solvent moieties, these porous solid solvents (PSSs) retain solvation ability, which greatly influences the performance of incorporated active sites via concerted non-covalent substrate–catalyst interactions. As a proof-of-concept, the -SO(3)H-incorporated PSSs exhibit high yields of fructose to 5-hydroxymethylfurfural in THF, which exceeds the best results reported using readily separable solvents and even rivals those in ionic liquids or DMSO. Given the wide application, our strategy provides a step forward towards sustainable synthesis by eliminating the concerns with separation unfriendly solvents.